Android-Based Media in Course of Mathematics Learning Strategy at Universitas Muhammadiyah Sumatera Utara - Ammy, Putri Maisyarah; Maryanti, Indra (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
This research is motivated by teaching materials used by lecturers in the learning process that have not instilled student interest in learning, so students have difficulty understanding the material provided during distance learning (online). This study aims to design android-based mathematics learning media in mathematics learning strategy courses. This Android-based mathematics learning media design model uses Research and Development (RD) developed by Borg and Gall. The product trial population in this study was students at the Universitas Muhammadiyah Sumatera Utara majoring in mathematics education using an instrument in the form of a questionnaire. This trial went through three stages, namely individual group trials, small group trials, and field trials. Before product testing, expert validation tests were carried out on the content and design of mathematics learning media using questionnaires according to predetermined indicators, then after that, a questionnaire analysis was carried out to see the percentage and validation criteria of mathematics learning media. This study designed android-based mathematics learning media that has been declared valid and suitable for use by 3 material experts who obtained an average score of 3,73 (valid) and 2 programming experts with an average score of 3,87 (valid). So, it can be concluded that android-based mathematics learning media is valid and feasible to be used as a mathematics learning media. The results of this research can be applied in the process of distance learning (online) and face-to-face to further increase student enthusiasm for learning.Penelitian ini dilatarbelakangi oleh bahan ajar yang digunakan dosen dalam proses pembelajaran yang belum menanamkan minat belajar mahasiswa, sehingga mahasiswa mengalami kesulitan untuk memahami materi yang diberikan selama pembelajaran jarak jauh (online). Penelitian ini bertujuan untuk merancang media pembelajaran matematika berbasis android pada mata kuliah strategi pembelajaran matematika. Model perancangan media pembelajaran matematika berbasis android ini menggunakan Research and Development (RD) yang dikembangkan oleh Borg and Gall. Populasi uji coba produk dalam penelitian ini adalah mahasiswa Universitas Muhammadiyah Sumatera Utara jurusan pendidikan matematika dengan menggunakan instrumen berupa angket. Uji coba ini melalui tiga tahap, yaitu uji coba kelompok individu, uji coba kelompok kecil, dan uji coba lapangan. Sebelum dilakukan pengujian produk terlebih dahulu dilakukan uji validasi ahli terhadap isi dan desain media pembelajaran matematika menggunakan angket sesuai indikator yang telah ditentukan, kemudian setelah itu dilakukan analisis angket untuk melihat persentase dan kriteria validasi media pembelajaran matematika. Penelitian ini merancang sebuah media pembelajaran matematika berbasis android yang telah dinyatakan valid dan layak digunakan oleh 3 orang ahli materi yang memperoleh skor rata-rata 3,73 (valid) dan 2 orang ahli pemprograman dengan perolehan skor rata-rata 3,87 (valid). Sehingga dapat disimpulkan bahwa media pembelajaran matematika berbasis android valid dan layak digunakan sebagai media pembelajaran matematika. Hasil penelitian ini dapat diterapkan dalam proses pembelajaran jarak jauh (online) maupun tatap muka agar lebih meningkatkan semangat belajar mahasiswa.